2023
DOI: 10.1111/ijn.13183
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses' psychological capital: A scoping review

Abstract: AimsThe aim was to examine the extent and scope of empirical research concerning registered nurses' psychological capital.BackgroundIn a time of global nursing shortage, identifying variables that could positively contribute to the retention of the nursing workforce is essential. Prior research has shown that psychological capital correlates positively with employees' better performance and well‐being.DesignA scoping review.Data sourcesA systematic literature search was conducted in the following databases: Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…Initially, Luthans introduced psychological capital to explain the positive mental abilities of employees ( 1 ), which refers to a type of positive mental energy expressed in the growth and development of an individual, indicating an individual’s motivational tendencies, and is a higher-order composite multidimensional structure generated through positive mental structures. Previous studies have demonstrated that nurses’ psychological capital is positively correlated with desired work-related outcomes such as work engagement, job satisfaction, organizational commitment, and innovative behaviors ( 2 ). Higher psychological capital was also associated with lower undesirable work-related outcomes like burnout and turnover intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, Luthans introduced psychological capital to explain the positive mental abilities of employees ( 1 ), which refers to a type of positive mental energy expressed in the growth and development of an individual, indicating an individual’s motivational tendencies, and is a higher-order composite multidimensional structure generated through positive mental structures. Previous studies have demonstrated that nurses’ psychological capital is positively correlated with desired work-related outcomes such as work engagement, job satisfaction, organizational commitment, and innovative behaviors ( 2 ). Higher psychological capital was also associated with lower undesirable work-related outcomes like burnout and turnover intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a large cross‐sectional survey ( n = 4677), higher psychological capital promoted nurses' innovative behaviour (Yan et al., 2020 ). A scoping review of nurses' psychological capital shows that psychological capital is associated with many positive work‐related outcomes (Flinkman et al., 2023 ). However, few studies included in this review reported the relationship between psychological capital and nurses' innovative behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological capital referred to a positive psychological state developed by individuals during their growth and developmental process (Chiang et al, 2023). It encompassed four core components: hope, self-efficacy, resilience, and optimism (Flinkman et al, 2023;Yuan et al, 2023). Previous studies have indicated that psychological capital had a significant positive impact on individuals' attitudes, behaviors, and performance (Lee et al, 2022).…”
Section: Introductionmentioning
confidence: 99%